2011
DOI: 10.1002/pon.2000
|View full text |Cite
|
Sign up to set email alerts
|

Understanding sleep disturbances in African‐American breast cancer survivors: a pilot study

Abstract: Objectives The goals of this study were (i) to report the prevalence and nature of sleep disturbances, as determined by clinically significant insomnia symptoms, in a sample of African-American breast cancer survivors; (ii) to assess the extent to which intrusive thoughts about breast cancer and fear of recurrence contributes to insomnia symptoms; and (iii) to assess the extent to which insomnia symptoms contribute to fatigue. Methods African-American breast cancer survivors completed surveys pertaining to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 41 publications
7
46
0
Order By: Relevance
“…Findings from this study suggest that, "I worry about my cancer coming back" better represents FCR (and potentially IT about cancer recurrence) for the participants than the cancer worry subscale as a whole. This significant result is confirmed by a previous pilot investigation (Taylor et al, 2012) that examined sleep disturbance in African American breast cancer survivors. Specifically, findings from Taylor et al (2012) indicated that intrusive thoughts related to cancer, which are a component of FCR, were a significant predictor of insomnia.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Findings from this study suggest that, "I worry about my cancer coming back" better represents FCR (and potentially IT about cancer recurrence) for the participants than the cancer worry subscale as a whole. This significant result is confirmed by a previous pilot investigation (Taylor et al, 2012) that examined sleep disturbance in African American breast cancer survivors. Specifically, findings from Taylor et al (2012) indicated that intrusive thoughts related to cancer, which are a component of FCR, were a significant predictor of insomnia.…”
Section: Discussionsupporting
confidence: 81%
“…This significant result is confirmed by a previous pilot investigation (Taylor et al, 2012) that examined sleep disturbance in African American breast cancer survivors. Specifically, findings from Taylor et al (2012) indicated that intrusive thoughts related to cancer, which are a component of FCR, were a significant predictor of insomnia. Results from the study reported here provide support to Lee-Jones and colleagues' (1997) multidimensional construct of FCR, including IT as a proposed mechanism for the relationship between FCR and poor sleep quality because of the significant relationship between the statement "I worry about my cancer coming back" and poor sleep quality.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…the results of taylor et al's studies indicate that respondents suffered from serious sleep disorders. Increase in insomnia symptoms occurred with negative thoughts about the cancer the respondent was diagnosed with [28].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in sleep have also been observed in a sample of presurgical breast cancer patients, the night prior to surgery intrusive thoughts were associated with less sleep duration and lower sleep efficiency (Wright, Schnur, Montgomery, & Bovbjerg, 2010). In breast cancer survivors, intrusive thoughts were shown to be related to self-reported symptoms of insomnia (Taylor et al, 2012).…”
Section: Cancer-related Stress and Physiological Disruption (Figure 1mentioning
confidence: 99%